BAUM TESTI PSIXOKORREKCIYALÍQ HÁM ARTTERAPIYALÍQ ILAJ SÍPATÍNDA - Turdımuratova, A.B. (SCIENCE and SOCIETY, 2025)
This article presents a comprehensive analysis of the projective psychodiagnostic method known as the Baum Test (tree drawing test), which is employed to assess the psycho-emotional characteristics, self-esteem levels, and mental well-being of minors. The significance of this technique is substantiated within the contexts of educational, clinical, corrective, and art-therapeutic practices. The paper examines key aspects of diagnostic administration, interpretative frameworks, and the potential application of the method in cross-cultural research. A review of contemporary scholarly literature is provided, highlighting both the diagnostic value of the Baum Test and its limitations, including the subjectivity of interpretation and the lack of full standardization. The study concludes with an emphasis on the necessity of a comprehensive and professional approach to the use of projective tools in psychological assessment.